ADVANCES IN THE SYNTHESIS AND CHEMISTRY OF ARYLHYDRAZONALS DERIVATIVES AS KEY PLAYERS IN MEDICINAL CHEMISTRY AND BIOLOGICAL SCIENCE - Mohamed R. Eletmany; Islam M. Abdellah (Chelonian Research Foundation, 2023)
This review analyses the chemical characteristics of arylhydrazonals in depth, with a particular emphasis on their critical function in heterocyclic synthesis. Arylhydrazonals are bidentate electrophilic substances that exhibit tridentate properties under certain functional group configurations. This review thoroughly examines the production processes and reactivity of these chemicals. The importance of arylhydrazonals in a variety of fields such as pharmaceuticals, agriculture, materials research, and catalysis are emphasized. Arylhydrazones emerge as essential intermediates in heterocyclic synthesis, exhibiting versatility in cyclization reactions as well as susceptibility to both nucleophilic and electrophilic processes. The review gets into the technical intricacies of arylhydrazonal preparation methods, with a particular emphasis on their synthesis from aldehydes, ketones, esters, enaminones, hydrazones, and hydroxymethyl derivatives. The adaptability of arylhydrazonals in nucleophilic addition processes is enhanced, allowing for the rapid synthesis of complex molecular structures. Because of their electrophilic reactivity, arylhydrazonals are useful in medicines, materials science, and catalysis. Furthermore, the review goes into arylhydrazonal potential for the synthesis of five and six-membered ring heterocycles such as 1,2,3-triazoles, pyrazoles, and pyridazines. The malleability of arylhydrazonals as intermediates finds a compromise between simplicity and complexity, opening the door to a broad range of heterocyclic compounds. Finally, thorough investigation of the chemistry of arylhydrazonals establishes them as flexible building blocks in the synthesis of varied heterocyclic structures, contributing to advances in a variety of scientific and industrial sectors. Keywords: Arylhydrazonals; Synthesis; Biological activity, hydrazones, enaminones.